2008
DOI: 10.2174/187221208784705251
|View full text |Cite
|
Sign up to set email alerts
|

Size Fractionation by Slalom Chromatography and Hydrodynamic Chromatography

Abstract: Hydrodynamic chromatography, also called separation by flow, is based on the use of the parabolic flow profile occurring in open capillaries or in the pores from a column filled with non-porous particles. The hydrodynamic chromatography separation medium, if any, is much simpler than that from size exclusion chromatography (porous particles), the former technique being used in the size-fractionation of many colloids and macromolecules. The transition between hydrodynamic chromatography (obtained using low flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
(187 reference statements)
0
5
0
Order By: Relevance
“…22. The authors (Couto et al, 2011) suggested that this behaviour can be explained by the theory that supports the hydrodynamic fractionation (Tijssen et al, 1986;Stegeman et al, 1993;Dias, 2007Dias, , 2008 and by the formation of a cell-free layer adjacent to the walls of the capillaries. …”
Section: Capillary Networkmentioning
confidence: 99%
“…22. The authors (Couto et al, 2011) suggested that this behaviour can be explained by the theory that supports the hydrodynamic fractionation (Tijssen et al, 1986;Stegeman et al, 1993;Dias, 2007Dias, , 2008 and by the formation of a cell-free layer adjacent to the walls of the capillaries. …”
Section: Capillary Networkmentioning
confidence: 99%
“…Figures 8 and 9 suggest that the RBCs velocities close to the microchannel wall are higher than that obtained with the numerical models since slip at the walls of the channel was assumed to be non-existent in the latter case. It is well know, in microcirculation and other areas [4,5,13,20,28,32], that RCBs, macromolecules, colloids, etc., are excluded from the region of the channel with low velocity and this may explain the observed differences.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the elements was fixed after a grid independence test. The grids were successively refined and the velocity obtained with the different meshes were compared, the results being considered independent of the mesh when a difference bellow 1% was achieved [4,[8][9][10].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…(3)) [9,10]. It is important to note As happens in granular beds [13][14][15][16], the flow in chevron-type passages is highly tortuous (see Fig. (4)).…”
Section: Gasketed Plate and Frame Heat Exchangersmentioning
confidence: 96%
“…(5) it is shown the location of protrusions (16) and recesses (17) and contact points (15), these points being generated by the conventional corrugations ( (12) and (13)) when two plates are pressed together to form a channel. The projections (16) and recessions (17) are located between the contact points (15). The difference between conventional chevron-type plate heat exchangers channels and the channels obtained with the disclosed plates may be better seen in Fig.…”
Section: New Plates For Plate Heat Exchangersmentioning
confidence: 99%